FEASIBILITY STUDY OF PT MELALI REALTYâS VILLA PROJECT IN SEMINYAK, BALI - Anthony, Darren
The tourism industry in Bali, a cornerstone of the local economy, experienced a severe downturn due to the COVID-19 pandemic, leading to declines in both tourist arrivals and accommodations. However, the sector has witnessed a robust recovery, with tourist arrivals now exceeding pre-pandemic levels. Despite this resurgence, the recovery of accommodation facilities has lagged, creating a discernible disparity in the market. This gap presents a significant opportunity for new investments in high-quality accommodations. PT MELALI REALTY, recognizing this opportunity, aims to leverage its existing land in the prime tourist area of Seminyak to develop a luxury villa, targeting the middle-to-upper segment of the recovering tourist market. The planned investment for this initiative is IDR 2,227,435,605, fully financed through equity. This study aims to determine the financial feasibility and identify potential risks of the project.